Crop residue in agriculture and its role in environment conservation - Singh, Geeta (Indian Farming, 2015)
Burning of crop residues results in loss of macro and micronutrients contained in the biomass. Therefore, burning of residues needs to be discouraged. In certain regions of our country, rice, wheat, maize, sorghum, fingermillet and pearlmillet residues are used as cattle fodder. Cotton, chilli, pulses and oilseeds residues find their use as household fuel. Rice husk is mainly used in boilers as fuel and bagasse, for paper and board production and power. To avoid crop residue burning, suitable technologies to harness them for various other uses and educative programmes need to be prepared to make people aware about the importance of crop residues.